Earning Per Share Memoderasi Pengaruh Debt to Equity Ratio terhadap Harga Saham di Bursa Efek Indonesia - Guntar Mahardika; Sonny Hersona; Nunung Nurhasanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of Debt To Equity Ratio (DER) on Stock Prices with Earning Per Share (EPS) as a moderating variable. The data used in this study are secondary data on the IDX and the company's annual report. The population used in this study was conducted on Textile and Garment Sub-sector companies listed on the IDX for the period 2012-2019. The analytical technique used is the MRA (Moderated Regression Analysis) test. The results showed that DER did not affect stock prices. EPS has an effect on stock prices. Testing the moderating variable in this study shows that EPS moderates the effect of DER on stock prices. The moderation test shows that a higher EPS value will be stronger in mitigating the effect of DER on stock prices. Keywords: Debt to Equity Ratio, Earning Per Share and Stock Price.